Vanligaste diagnoserna hos svenska travhästar - Skutnabb, Tamara (2020)
Due to a successful breeding process the fastest trotters will within 50 years run at the speed of 1.09 from volt start. Harness racing is a popular sport and a big industry in Sweden with 850 different racing events and 903 million SEK in purse money annually. Consequently, owners and trainers of racehorses want to see their protegees race. The most common cause for a harness racing horse to either end their career or require convalescence are various kinds of injuries which require veterinary assistance. Animal welfare is an important issue to the Swedish Trotting Association. The association wished to obtain knowledge of common injuries in Swedish harness racing horses in order to continue to develop their contribution to the animal welfare. The aim of this study was to find out which injuries are most common in Swedish harness racing horses. Earlier international studies have shown the most common injuries to be those of carpal and fetlock joint lameness. The material used in this study was collected of equine patient records from six different veterinary clinics in various locations in Sweden. It contained a total of 8 742 diagnosis from the years 2016 to 2018. The information gathered of each equine patient are the type of diagnose, age, gender, race and trainer status. The differences between the results were measured by a p-value. The result was significant at p-value <0,05. The result was very significant at p-value <0,001 and tendencies to be significant at p-value <0,07. The result of the study showed that carpal and fetlock joint lameness were the most common injuries among harness racing horses also in Sweden. It also showed that stifle joint lameness and problems related to the mouth were frequent. When comparing trainer status, age and race of the equine patient there were differences to be seen in the injury picture. As conclusion injuries among harness racing horses are common. Among the main factors are that all racehorses are trained and raced in a relatively the same manner and under similar conditions, therefore their injuries are also the same. Furthermore, the racing horse has in most cases evolved largely in a very short time hence knowledge and science have not developed at the same pace.